Will executive equity incentives affect investor relations management: Empirical evidence from Chinese listed companies - Shi, Xiaofei; Liu, Zunhu; Wang, Yuanfang (Frontiers in Psychology, 2022)
How to improve the level of investor relationship management of listed companies and establish trust relationship with investors is an important research issue for enterprises in the capital market. From the perspective of optimal contracting theory, we construct a theoretical model to assess how executive equity incentive plans (EEIPs) affect enterprises’ investor relationship management. Based on the panel data of Chinese A-share listed companies from 2014 to 2019, our baseline results indicate that EEIPs improves investor relations. This positive effect mainly exists in stock options, rather than restricted stocks. In the sample of enterprises implementing EEIPs, the intensity of executive equity incentive is positively correlated with investor relationship management. Further research shows that EEIPs mainly through telephone communication, network communication and on-site communication to achieve the impact of listed companies investor relationship management.These findings enriches the economics of executive equity incentives from the perspective of investor relations management. At the same time, it has certain guiding significance for improving the design of the incentive system for corporate executives and improving the information efficiency of the capital market.